OPTIMIZATION PROGRAM DESIGN AND RESEARCH OF ANGULAR CONTACT BALL BEARING CHANNEL CURVATURE RADIUS - DENG Tao; WU KaiSong; AN Mei; YAN CaiXiu; ZOU MingMing (Jixie qiangdu)
Firstly the theory of Hertz was used to calculate the maximum stress of same angular contact ball bearings in the same condition and different internal and external channel curvature radius. And ANSYS APDL parametric language was used to establish three-dimensional finite element model of angular contact ball bearing and the model considers the radial clearance and axial clearance. ANSYS / LS-DYNA was used to load pre-tightening force,radial force,axial force and inner rotation on bearing.And comparative study on the theoretical analysis and finite element analysis was made to verify the validity of the finite element analysis. Finally,maximum stress of angular contact ball bearing was obtained in the different internal and external channel curvature,in order to provide scientific reference for the selection of channel curvature radius of angular contact ball bearings.